2014
DOI: 10.1097/jsm.0000000000000021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Physiotherapy Program Versus Dexamethasone Injections for Plantar Fasciopathy in Prolonged Standing Workers

Abstract: Workers standing for prolonged periods experienced the same short-term therapeutic effectiveness with a physiotherapy-led exercise program compared with an injection of corticosteroid with stretching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…(7) One study (18) reported better results in the botulinum toxin A injection group (intervention group) compared to the corticosteroid injection group. The remaining four studies (15,16,19,21) showed significant pain reduction in both intervention groups at follow-up intervals when compared to baseline but no significant differences between the intervention groups.…”
Section: Patient-assessed Outcome: Foot Painmentioning
confidence: 99%
See 4 more Smart Citations
“…(7) One study (18) reported better results in the botulinum toxin A injection group (intervention group) compared to the corticosteroid injection group. The remaining four studies (15,16,19,21) showed significant pain reduction in both intervention groups at follow-up intervals when compared to baseline but no significant differences between the intervention groups.…”
Section: Patient-assessed Outcome: Foot Painmentioning
confidence: 99%
“…Five RCTs explored the use of long-acting corticosteroids, i.e. dexamethasone (14,16,18) and betamethasone, (17,19) while the other five investigated the use of intermediate-acting corticosteroids, i.e. methylprednisolone, (13,15,21) prednisolone (7) and triamcinolone.…”
Section: Corticosteroid Injectionsmentioning
confidence: 99%
See 3 more Smart Citations